Diagnóstico sectorial de la actividad de transporte en camionetas de pasajeros y carga por carretera, del distrito 11D06, de la provincia de Loja. - Alvarez Rey, Edwin Ramsés (2024)
Sector diagnosis is a tool to evaluate a specific sector, providing an analysis of key aspects of organisations, identifying strengths and weaknesses, facilitating informed and strategic decision-making. The purpose of this research is to carry out a sector diagnosis of the cooperatives and van companies in District 11D06 of Loja province, to obtain an objective view of the current state of the organisations, in order to provide recommendations to optimise the functioning and competitiveness of the sector through operational efficiency, innovation, quality of service, and profitability for the benefit of its members. The process was developed through a mixed approach combining qualitative and quantitative methods to analyse financial and non-financial data from 13 transport cooperatives operating in ISIC activity H4923.01. Among the outstanding results, it can be seen that the companies analysed have an average liquidity level of 4.46; manage a working capital of $727.80, show efficiency in the use of their assets with a return on assets (ROA) of 51%, have a level of indebtedness below the average, which indicates that the companies predominate with their own capital, in the non-financial area, have an average of 46% effectiveness in the control of vehicles and 39% in the renewal of fleets, likewise the continuous training of partners and administrative personnel has guaranteed the provision of an efficient service. Finally, it was highlighted that the profitability for the partners reaches a margin of 76%, due to an adequate management of expenses, emphasising the economic solidity of the sector. The research concluded that companies in the transport sector play a fundamental role in the local economy, maintain good organisational performance, demonstrate high liquidity, low indebtedness and efficient administrative management, which reflects good profitability for the members of the transport cooperatives.